2009
DOI: 10.2136/vzj2008.0062
|View full text |Cite|
|
Sign up to set email alerts
|

Revisiting Vereecken Pedotransfer Functions: Introducing a Closed‐Form Hydraulic Model

Abstract: We revisited the Vereecken database, which has been used to derive pedotransfer functions (PTFs) to estimate the soil hydraulic parameters of Belgian soils. We developed new PTFs based on the Mualem–van Genuchten model, constraining m = 1 − 1/n and using fewer parameters. The goodness‐of‐fit was similar to the one originally obtained by Vereecken. We used a one‐step procedure that allows direct quantification of the correlation matrix and the uncertainties of the estimated parameter values. The coefficients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
218
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(226 citation statements)
references
References 36 publications
(50 reference statements)
3
218
2
3
Order By: Relevance
“…While it has been previously demonstrated that water flow in macropores cannot be accurately predicted with empirical models from basic soil properties (Weynants et al, 2009;Vereecken et al, 2010), there is only little published work related to gas diffusivity. Furthermore, existing pedotransfer functions/empirical models do not discern between matrixand biopore-dominated flow domains, which is of significance for understanding and accurate prediction of preferential flow as demonstrated in the results section.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been previously demonstrated that water flow in macropores cannot be accurately predicted with empirical models from basic soil properties (Weynants et al, 2009;Vereecken et al, 2010), there is only little published work related to gas diffusivity. Furthermore, existing pedotransfer functions/empirical models do not discern between matrixand biopore-dominated flow domains, which is of significance for understanding and accurate prediction of preferential flow as demonstrated in the results section.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods are indirect, allowing a theoretical calculation of the function K(θ) from water retention data in the soil obtained in the laboratory Weynants et al, 2009). Both the direct and indirect methods are time-intensive, generate costs due to the need for pre-determinations of hydraulic properties, are error-prone, and the results are only valid on a local scale (Mermoud & Xu, 2006;Arya & Heitman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…K* (l T -1 ) is a matching point hydraulic conductivity for S e = 1. Although K* is usually deemed as the saturated hydraulic conductivity Ks, a fitted matching point conductivity for slightly unsaturated conditions, K*= K 0 <Ks, may be preferable for modelling unsaturated soils (Weynants et al, 2009).…”
Section: Methodsmentioning
confidence: 99%